2020
DOI: 10.15560/16.1.219
|View full text |Cite
|
Sign up to set email alerts
|

First country record of Trachycephalus mesophaeus (Hensel, 1867) (Amphibia, Anura, Hylidae) in Argentina

Abstract: We report the first record of the Porto Alegre Golden-eyed Treefrog, Trachycephalus mesophaeus (Hensel, 1867), from Argentina based on a single specimen collected in the 1980s at Las Lomitas, province of Formosa, northeastern Argentina. This new record, within the Chacoan Biogeographical Region, is separated by more than 1300 km from its main range in the Atlantic Forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…1 A-D) is a species known to occur in the Atlantic Forest of Southeastern and Eastern Brazil, from the states of Rio Grande do Sul to Pernambuco (e.g., Kwet et al, 2010;Haddad et al, 2013). Garcia-Marsà et al (2020) identified the specimen explicitly based on color pattern, and, very likely (see below) on the fact that the specimen had a label identifying it as "Trachycephalus sp." The authors pondered the possibility that it could belong to "a still unknown population of the T. typhonius complex".…”
Section: The New Recordmentioning
confidence: 99%
See 2 more Smart Citations
“…1 A-D) is a species known to occur in the Atlantic Forest of Southeastern and Eastern Brazil, from the states of Rio Grande do Sul to Pernambuco (e.g., Kwet et al, 2010;Haddad et al, 2013). Garcia-Marsà et al (2020) identified the specimen explicitly based on color pattern, and, very likely (see below) on the fact that the specimen had a label identifying it as "Trachycephalus sp." The authors pondered the possibility that it could belong to "a still unknown population of the T. typhonius complex".…”
Section: The New Recordmentioning
confidence: 99%
“…indicated that the specimen was accessioned as part of material sporadically donated by the collector. Clearly, at some point, there was a human error, the label was associated with the wrong specimen, and triggered a series of confusions that ended up with Garcia-Marsà et al (2020) wrongly reporting T. mesophaeus for the first time in Argentina. Nevertheless, the fact that the manuscript reporting the "new" record, including illustrations of the remarkably misidentified specimen, found its way through the conventional filters of scientific publication, is worrisome.…”
Section: Layers Of Confusionmentioning
confidence: 99%
See 1 more Smart Citation